Systemic Issues And Emotional Compliance To Pandemics In South African Schools: A Policy Flaw Or Foresight Deficit In The Case Of The Emergence Of The Novel Coronavirus (Journal of Pharmaceutical Negative Results, 2023)
It is no doubt that the outbreak of the novel coronavirus caught the world including South Africa, off-guard. This statement refers in particular, to the fact that the outbreak of the pandemic firstly exposed the level of unpreparedness of government and its different departments, including the private sector to deal with unforeseen outbreaks like the coronavirus which leads to COVID-19. This is a typical example of systemic problems within the government and the private sector. Secondly and most importantly, this outbreak exposed the level of inequality between schools in rural areas and those in townships and affluent parts of the country which are mostly habited by black middle class and white people. The purpose of this paper is to investigate the systemic challenges and the emotional impact of this virus on the learners and their parents; the learners and their teachers, and to venture into the policymaking and implementation terrain of the Department of Basic education with a specific focus on how the DBE responded to the outbreak. Furthermore, this paper makes a case out of the emerging case by case approach of the government and the DBE in dealing with the threats which are posed by this pandemic to communities and schools. The researchers hold the view that this paper will expose the levels of inequality between schools in different parts of the country and advocate for a culture of foresight in the education management system; a culture that acknowledges that schools, like communities and business entities, are vulnerable and susceptible to external forces that may have long-lasting effects on their functionality.